Thunder in space - Del Rey, Lester, 1915-1993; Finlay, Virgil, 1914-1971 (Salt Lake City, UT : Project Gutenberg, 2023)
"Thunder in Space" by Lester Del Rey is a science fiction novel written in the early 1960s. The narrative is set against the backdrop of the Cold War, exploring the tensions between the United States and the Soviet Union as they navigate the treacherous landscape of military power in space. The book addresses the critical issues of nuclear arms, international relations, and the burdens of scientific advances intertwined with political maneuverings in a time of escalating crisis. The story centers around the American space station, the "Goddard", and its crew, who are grappling with the complexities of their situation as the threat of nuclear war looms large. The protagonist, Jerry Blane, finds himself unexpectedly in command as tensions escalate following the destruction of Soviet supply ships. As radiation levels from nuclear warheads begin to rise alarmingly, a series of events unfold that lead to a race against time to avert disaster. Amidst these challenges, Blane discovers the possibility of cooperation with their Russian counterparts, highlighting the potential for peace in an era fraught with conflict. Ultimately, the narrative culminates in a pivotal decision that could reshape humanity's trajectory in space, as both nations are forced to confront their escalating fears and the fragility of their coexistence. (This is an automatically generated summary.)
Release date is 2023-12-01
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Space stations -- Fiction; Weapons -- Fiction; Cold War -- Fiction